Recording of brain activity across spatial scales. (June 2015) - Lewis, CM; Bosman, CA; Fries, P
Highlights: Brain activity is highly structured within local and distributed circuits. Understanding brain function requires simultaneous recording across spatial scales. Multi-electrode arrays allow targeted recording from local and distributed circuits. Wide sampling allows identification of distributed networks and topographic mapping. Targeted dense recording allows integration of local and distributed dynamics. Abstract : Brain activity reveals exquisite coordination across spatial scales, from local microcircuits to brain-wide networks. Understanding how the brain represents, transforms and communicates information requires simultaneous recordings from distributed nodes of whole brain networks with single-cell resolution. Realizing multi-site recordings from communicating populations is hampered by the need to isolate clusters of interacting cells, often on a day-to-day basis. Chronic implantation of multi-electrode arrays allows long-term tracking of activity. Lithography on thin films provides a means to produce arrays of variable resolution, a high degree of flexibility, and minimal tissue displacement. Sequential application of surface arrays to monitor activity across brain-wide networks and subsequent implantation of laminar arrays to target specific populations enables continual refinement of spatial scale while maintaining coverage.